2015
DOI: 10.7717/peerj.1200
|View full text |Cite
|
Sign up to set email alerts
|

Fear of becoming pregnant among female healthcare students in Spain

Abstract: The inconsistent use of hormonal contraceptive methods can result, during the first year of use, in one in twelve women still having an undesired pregnancy. This may lead to women experiencing fear of becoming pregnant (FBP). We have only found one study examining the proportion of FBP among women who used hormonal contraceptives. To gather further scientific evidence we undertook an observational, cross-sectional study involving 472 women at a Spanish university in 2005–2009. The inclusion criteria were havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…In addition, all the participants had to have had vaginal intercourse with a man during the three months prior to completing the questionnaire and not have a stable partner; i.e., have had at least one sexual encounter with someone she did not identify as a stable partner and this partner was open to sexual activities with others. This information was assessed by specific questions, shown in the Appendix of a previous paper ( Navarro-Cremades et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, all the participants had to have had vaginal intercourse with a man during the three months prior to completing the questionnaire and not have a stable partner; i.e., have had at least one sexual encounter with someone she did not identify as a stable partner and this partner was open to sexual activities with others. This information was assessed by specific questions, shown in the Appendix of a previous paper ( Navarro-Cremades et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…The information was collected with an original questionnaire (See Appendix in Navarro-Cremades et al, 2015 ). Prior to distributing the questionnaire, a verbal introduction was given explaining the voluntary and anonymous nature of the survey, as well as the confidentiality of all the data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this pilot study showed the good psychometric characteristics of the questionnaire (analysis of items and internal consistency, indexes of discrimination and factorial analysis) (Van-der Hofstadt et al, 2007Hofstadt et al, -2008Navarro-Cremades et al, 2013). The questionnaire used in this study collected information about various female sexological aspects (Van-der Hofstadt et al, 2007Hofstadt et al, -2008Navarro-Cremades et al, 2013;Navarro-Cremades et al, 2015). This study only used those items considered most relevant by the research team.…”
Section: Study Populationmentioning
confidence: 99%
“…To assess this, questions were asked about contraception methods used ( Manuscript to be reviewed frequency of sexual activities (yes and no), desire to have more variety in sexual activities (hour of the day, position, etc.) (yes and no), frequency of sexual intercourse with the partner (6 5-7 times/week; 5 3-4 times/week; 4 1-2 times/week; 3 2-3 times/month; 2 once/month), and age (in years) (Navarro-Cremades et al, 2015).…”
Section: Study Populationmentioning
confidence: 99%